ASSESSING THE IMPACT OF NON-TEST EVALUATION ON NATIONAL INSIGHT DEVELOPMENT: A TRAINING PERSPECTIVE - Ahmad Almarisi; Dewa Agung Gede Agung (Universitas Negeri Medan, 2024)
This study aims to deeply understand the impact of non-test evaluation on the development of national awareness from a training perspective. Using a qualitative approach with a case study design, this research focuses on the experiences, perceptions, and views of training participants and trainers regarding the use of non-test evaluation. The study is conducted at several training institutions that offer national awareness development programs, with participants consisting of training attendees and trainers selected through purposive sampling. The research instruments include in-depth interviews to explore the views and experiences of participants and trainers, participatory observation to directly observe the training process and interactions that occur, and the collection of documentation such as training modules, evaluation reports, and non-test evaluation materials. The data obtained are analyzed using thematic analysis techniques to identify themes and patterns from the interviews, observations, and documentation. The findings of this study are expected to provide new insights into the effectiveness of non-test evaluation in enhancing the understanding and appreciation of national awareness among training participants. Additionally, this research aims to provide recommendations for developing more effective evaluation methods in the context of national awareness training. To ensure the validity and reliability of the research results, data triangulation is conducted by comparing and integrating findings from various data sources. The results of this study are expected to provide a comprehensive and in-depth understanding of the impact of non-test evaluation on the development of national awareness and serve as a reference for education and training practitioners in designing more effective evaluations to facilitate the development of national awareness.